Sri Lanka : From Peace Dividend to Sustained Growth Acceleration - Fonseka, Daminda; Pinto, Brian; Prasad, Mona; Rowe, Francis (World Bank, Washington, DC, 2013)
Following the cessation of hostilities in May 2009, the Government of Sri Lanka has announced a suitably ambitious macroeconomic vision to capitalize on the peace dividend. Its goals include growing at 8 percent or more per year and lowering government indebtedness from around 80 to 60 percent of GDP by 2015. This paper's main finding is that while some post-conflict bounce is only to be expected, sustaining high growth presents significant challenges. A substantial rise in the national investment and savings rates will be needed to sustain growth rates of 8 percent even when accompanied by a significant rise in total factor productivity growth. With the government's balance sheet constrained by its desire to lower public indebtedness, private investment will need to become the engine of growth. This places high priority on better infrastructure, clear signals about the relative roles of the public and private sectors, and hard budget constraints and competition both to strengthen the investment climate and spur technological upgrading in pursuit of faster productivity growth.